Influence of Drying Conditions on Physicochemical, Phytochemical, and Antioxidant Properties of Medicinal Plant Stem Xáo Tam Phân (Paramignya trimera) Grown in Vietnam - Nguyen, Van Tang; Tran, Thanh G.; Nguyen, Van-Thi; Tran, Ngoc Le; Nguyen, Van Hoa (Current Nutrition & Food Science, 2024)
Introduction: This study aimed to assess the physicochemical, phytochemical, and antioxidant properties of medicinal plant stem Xáo tam phân (Paramignya trimera) as influenced by 11 drying conditions. Xáo tam phân (Paramignya trimera (Oliv.) Guillaum) has been used in fold medicine for cancer prevention and treatment. The preparation of the dried sample is crucial and necessary for further investigation and application. To evaluate the effects of some popular drying methods, namely, sun drying, hot-air drying, microwave drying, infrared drying, and freeze drying on the physicochemical properties, the retention of phytochemical compounds (total saponins, phenolics, and flavonoids), and antioxidant properties (DRSC, CUPRAP, and FRAP) of dried P. trimera stem. Methods: The plant stem Xáo tam phân (Paramignya trimera) was dried by 11 drying conditions: sun drying at 36.6°C; hot-air drying at 60°C, 80°C, and 100°C; microwave drying at 270 W, 450 W, and 720 W; infrared drying at 40°C, 45°C, and 50°C; and freeze drying at -40°C. Results: The results show that among the 11 drying conditions used, hot-air drying at 80°C achieved the highest phytochemical contents of the P. trimera stem in terms of total saponins (28.82 mg EE/g DS), total phenolics (3.71 mg GAE/g DS), and total flavonoids (10.82 mg CE/g DS), and infrared drying at 50°C possessed the greatest antioxidant activity of the P. trimera stem (3.59 and 9.56 mg TE/g DS for DRSC and CUPRAC, respectively); however, both these drying methods had the longest drying time (1.5 to 7.0 h.) and consumed the highest energy (2.10 to 11.77 kWh). In contrast, microwave drying took the shortest drying time (0.1 to 0.4 h.) and consumed the least energy (0.07 to 0.14 kWh), but it still retained moderate levels of phytochemical compounds and antioxidant activity of the P. trimera stem. Conclusion: The findings achieved from this study recommend using hot-air drying at 80°C for the preparation of the dried sample from the P. trimera plant stem.
Keywords: Paramignya trimera